Aksesibilitas Sumber Pakan Ternak Ruminansia pada Musim Kemarau di Daerah Pertanian Lahan Kering - Eka Handayanta; Endang Tri Rahayu; Mufti Ari Wibowo (Universitas Sebelas Maret (UNS), 2015)
This aim of this research to find out the level of easiness or difficulty of beef cattle farmers inobtaining feedstuff in the dry season in dry land farming area . The research was take place in thevillage of Kemejing, District of Semin, Gunung Kidul Regency, Yogyakarta from August to October(dry season). The research with survey method on the techniques of Participatory Rural Appraisal(PRA). Thirty (30) farmers as respondents, with 2-3 cows ownership provisions, and have a minimumof 2 years on the experience of raising cattle. Accessibility to sources of feedstuff were observedrelated to the origin of feed, feed resources and location distance or using time, purchase feeds,availability of labor and time needed in looking for feed. Results of the research were reported bydescriptive. The results showed that the average of the five observed variables, namely the origin offeed, distance and time, the purchase of feed, labor availability and the search time, obtained scoreare successively 0.77; 0.73; 0.96; 0.71 and 0.88, so that the total score was 4.05 and it is called ineasy criteria. The conclusion from this study is the accessibility of feed for cattle in dryland farmingareas in the dry season is easy.